Adult Education and The Scientific Community - Jesus Gomez-Alonso; Tere Sorde-Marti (Adult Education Research Conference, 2001)
In this paper, we analyzed the recent developments of the AE Scientific Community in Spain. Particularly, we focus in which factors have made possible to overcome its isolated initial situation towards a high quality one. Finally, we identified current works and future trends in order to characterized its main aspects such as its dialogic approach as a result of their interdisciplinary and interinstitutional efforts.